Distinctive Expression of Bcl-2 Factors in Regulatory T Cells Determines a Pharmacological Target to Induce Immunological Tolerance - Gabriel, Sarah Sharon; Bon, Nina; Chen, Jin; Wekerle, Thomas; Bushell, Andrew; Fehr, Thomas; Cippà, Pietro Ernesto (Frontiers in Immunology, 2016)
Distinctive molecular characteristics of functionally diverse lymphocyte populations may represent novel pharmacological targets for immunotherapy. The intrinsic apoptosis pathway is differently regulated among conventional and regulatory T cells. Targeted pharmacological modulation of this pathway with a small molecule Bcl-2/Bcl-xL inhibitor (ABT-737) caused a selective depletion of effector T cells and a relative enrichment of regulatory T cells in vivo. Treatment with ABT-737 resulted in a tolerogenic milieu, which was exploited to alleviate graft-versus-host disease, to prevent allograft rejection in a stringent fully MHC-mismatched skin transplantation model and to induce immunological tolerance in combination with bone marrow transplantation. This concept has the potential to find various applications for immunotherapy, since it allows pharmacologic exploitation of the immunomodulatory properties of regulatory T cells without the need for cell manipulation ex vivo.